2018
DOI: 10.1002/jor.23894
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps weakness preferentially predicts detrimental gait compensations among common impairments after total knee arthroplasty

Abstract: Patients with total knee arthroplasty (TKA) have large deficits in physical performance in comparison to their healthy age-matched peers. Limb asymmetry stemming from less relative load borne by the surgical limb during daily mobility is associated with diminished performance and worsens with greater mobility demands. How common targets of postoperative care, such as muscle weakness, lower limb extension power, residual knee pain, and poor balance confidence can influence asymmetrical limb loading remains uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Alternatively, movement symmetry retraining is rarely prescribed in standard rehabilitation practice and may provide an alternative intervention to incorporate pre- and post-TKA to maximize lower limb function, particularly in restoring quadriceps strength. Studies are showing promising evidence that movement symmetry retraining is beneficial in improving aberrant movement patterns following TKA [4446]. However, further prospective longitudinal designs are needed to determine long-term retention of improved movement quality and how motor retraining influences muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, movement symmetry retraining is rarely prescribed in standard rehabilitation practice and may provide an alternative intervention to incorporate pre- and post-TKA to maximize lower limb function, particularly in restoring quadriceps strength. Studies are showing promising evidence that movement symmetry retraining is beneficial in improving aberrant movement patterns following TKA [4446]. However, further prospective longitudinal designs are needed to determine long-term retention of improved movement quality and how motor retraining influences muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…2 n = repetition count of the test for each specimen. 3 Vastus medialis (VM) muscle force was set to zero (VM: 0 N; RF/VI: 49 N; VL: 45 N). 4 VM muscle force was set to normal muscle force (VM: 31 N; RF/VI: 49 N; VL: 45 N).…”
Section: Vm Impairment Repetition Count Total Test Countmentioning
confidence: 99%
“…TKA survival rates reportedly exceed 95% at 10 years and 90% at 15 years [1,2]. The Fourth American Joint Replacement Registry reported that TKAs were performed for approximately 0.5 million people in the USA in 2016 and will be performed in approximately 3 million people annually worldwide after 2030 [3][4][5]. However, TKA continues to exhibit failures generally related to pain, infection, osteolysis, wear, aseptic loosening, periprosthetic fracture, instability, or malalignment [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] The early restoration of the muscle contraction properties of the quadriceps is essential to ensure appropriate recovery and facilitate the return to the activities of daily living, as well as to work and/ or sports activities. [7][8][9] Among the various types of muscle contraction, maximal isometric strength (MIS, or maximal isometric voluntary contraction [MIVC]), is an essential parameter of strength for the correct functioning of the muscle motor unit. [10][11][12] Conditioned muscle inhibition can effectively decrease this variable.…”
Section: Introductionmentioning
confidence: 99%